IDENTIFIKASI KELEMAHAN METODE EARNED VALUE PADA PENGUKURAN KINERJA BIAYA DAN WAKTU PROYEK KONSTRUKSI - F., Fahirah; Wahyu Adi, Tri Joko; Anwar, Nadjadji (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2013)
Earned Value method (EV) has several weaknesses which makes it difficult to optimally apply in the construction projects. This study aims to identify the shortcomings of Earned Value related to the project cost and time performance. Literature study was conducted from the various sources related to the EV topic. The result shows that the main weakness of Earned Value method are: EV prediction method is assumed deterministic, linear, non-dynamic and does not accommodate uncertainty factors of time and cost of construction projects. Â  Keywords: constructionÂ  project, time and cost performance, earned value